Deformations of N=2 superconformal algebra and supersymmetric two-component Camassa-Holm equation - Aratyn, H.; Gomes, J. F.; Zimerman, A. H. (Iop Publishing Ltd, 2007)
This paper is concerned with a link between central extensions of N = 2 superconformal algebra and a supersymmetric two-component generalization of the Camassa-Holm equation. Deformations of superconformal algebra give rise to two compatible bracket structures. One of the bracket structures is derived from the central extension and admits a momentum operator which agrees with the Sobolev norm of a co-adjoint orbit element. The momentum operator induces, via Lenard relations, a chain of conserved Hamiltonians of the resulting supersymmetric Camassa-Holm hierarchy.